Recording educational information in medical record: the experience of a Rehabilitation Hospital. (13th November 2019) - Scarpis, E; Poletto, M; Guardini, I; Londero, C; Maestra, M R; Tea, G P; Zampa, A; Lattuada, L; Castriotta, L; Brusaferro, S
Abstract: Issue/Problem: Healthcare organizations have the responsibility to provide education to patients and families so that they have the knowledge to participate in the care process and make decisions. Rehabilitative organizations, on account of the long hospitalization period and the specific care plans, have to organize education resources in the most effective manner, ensuring the registration of what has been done in the medical record (MR). Description of the problem: During the accreditation process, IMFR (Medical and Physical Rehabilitation Institute - an hospital part of the Udine Healthcare Trust) launched a MR-quality program. A dedicated team of 3 doctors, 4 nurses and 4 therapists changed the way in recording educational information in MR, introducing in April 2018 a specific, independent form, part of the MR, where documenting the achievement of two educational phases: assessment and delivery. The aim of this project is to determine if the introduction of this specific educational form and its sharing process, included in the wider MR-quality program, would improve the recording behavior. Twenty MRs were quarterly analyzed from December 2017 to December 2018, assessing educational forms completeness. Significance (p < 0.01) was assessed by Cochran-Armitage test for trends. Results: The recording behavior improved significantly from 53% (21/40; Dec-17) to 88% (30/34) in June 2018, after the introduction of the specific education form and remained high also in Sept.2018 (90%, 34/38) and in Dec.2018 (82%, 31/38), with an overall trend of + 29%. Lessons: Sharing elements in the creation of the specific educational form with a multidisciplinary approach, within a wider MR-quality program, allows to improve the recording behavior of educational information in it. Hopefully this method would help healthcare professionals and organizations to ensure the education needed to patients and families. Key messages: A multidisciplinary approach is a good model to deal with specific aspects of quality programs. A specific form, part of the MR, allows to improve behavior in recording educational information.